Growth and Collapse of a Single Bubble near a Plate by Spark Discharge in Water. (November 2015) - Akcam, I; Inaba, K; Takahashi, K; Kishimoto, K
Abstract: Single bubble dynamics in the vicinity of a solid boundary submerged in water were studied experimentally. Single bubble inside a water tank was generated by a spark discharge of capacitor into a couple of copper wires closing a simple circuit. A circular polycarbonate plate was placed horizontally above the bubble creation site. Polycarbonate plates with two different thicknesses were tested by changing the distance between the plate and the creation site. The effects of distance to the wall and wall thickness on the bubble motion is observed by considering the fluid-structure interaction. It is shown that motion of the two boundaries during the bubble generation differ from each other. Jetting behavior of two cases is also different.